Degradation of Imidacloprid Residue on Red Tomatoes (Solanum lycopersicum) by Advanced Oxidation Processes and Analysis using Spectrophotometer and HPLC - Safni Safni; Hazanita Jumiaty; Hermansyah Aziz (Syarif Hidayatullah State Islamic University, 2021)
The insecticide imidacloprid (C9H10ClN5O2) common used by farmers to control pests on red tomato plants, is a dangerous substance classified as a Class II toxic. The imidacloprid residue in red tomatoes enters the body, it will lead to health problems. The purpose of this study was to determine the percentage of imidacloprid residue that can be degraded using the Advanced Oxidation Processes (AOPs) method, which includes sonolysis, sonozolysis, ozonolysis, ozone water, and the effect of various parameters. Processing time, water volume, and red tomato mass were the test parameters studied. The change in imidacloprid residue concentration during the degradation process was measured using a UV/Vis spectrophotometer (double beam) with a wavelength of 200-400 nm and HPLC with mobile phase composition used was acetonitrile/water (65:35 v/v). With a processing time of 10 minutes, the imidacloprid residue in red tomatoes can be degraded 57.38% by sonozonolysis, 63.51 % by sonolysis, 85.17 % by ozonolysis, and 88.76 % by ozone water. The imidacloprid residue in 75 g of red tomatoes could be removed as much as 91.65% by treating with ozone water for 15 minutes. HPLC analysis showed that no intermediate compounds were detected in the imidacloprid residue degradation process in red tomatoes.